THE INFLUENCE OF PHYSIOLOGICAL ASPECTS OF THE DEVELOPMENT OF THE CHILD'S BODY ON THE CHOICE OF MATERIALS FOR CHILDREN'S CLOTHING - Umida Tokhtasinovna Muminova (Journals Park Publishing, 2022)
In the modern world, the concept of "comfort" of clothing is inextricably linked with the safety of the product, since ensuring optimal indicators of properties characterizing the comfortable state of the body reflects its normal functioning. It should be noted that the design developments took into account those ergonomic requirements that are set out in the normative and technical documentation, but now the question is being raised about the design and creation of such industrial products and subject environment, with the use of which human activity becomes optimal, i.e. while ensuring high efficiency of activity, no harm will be caused to the physical health of a person
Keywords: comfortable, physiological, meteorological, physiology, clothing materials, thermoregulation, mechanism.